Sosialisasi bagi Para Orang Tua dalam Menghadapi Problematika Pembelajaran Jarak Jauh di Desa Keboan Kecamatan Ngusikan Jombang - Alifiyah Puspita Al Gholaini (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2021)
In the pandemic era, the implementation of online learning policies was also carried out in Keboan Jombang Village. As long as this home learning activity has been implemented until now, many parents of students have experienced problems when accompanying their children to study or do schoolwork at home. This online learning system is very confusing for parents due to several factors, including the lack of network availability or internet quota to support learning activities at home. This confusion is also increasingly felt by parents whose children are in Elementary School/Madrasah Ibtidaiyyah. Referring to government policy, online learning methods are considered to be very effective and efficient. However, in practice, parents still experience difficulties, especially when it comes to the use of information technology. Lack of understanding and knowledge in using it as a medium of learning encourages children's activities in doing tasks are also hampered. The subjects for Elementary School/Madrasah Ibtidaiyyah currently refer to the theme. This is also problematic for parents because the books provided by the school do not contain material on one theme completely. Because basically, referring to the objectives of the 2013 curriculum, it is expected that students will be able to develop and think critically from the material provided. The activity methods to be used include; maturation of concepts, preparation, implementation of activities, evaluation of activities, preparation of reports, and submission of reports. The responses from 20 participants consisting of parents who study at SDN Keboan and MI Al Hidayah Keboan can be described that the ability of parents or participants to understand and overcome problems in online learning before the socialization is held is quite minimal and after socializing the parents or participants seems to have improved quite well in understanding and overcoming the problems of online learning.